Salamon Market Alternatif Pasar Malam Di Lingkungan Urban - Winarno, Ari; Mustaqin, Khairul (ATRAT: Jurnal Seni Rupa, 2024)
The following written presentation is a track record of Community Service (PKM) activities that took place at Taman Griya Mitra Desa Cinunuk Cileunyi Bandung. The activities carried out were to optimize the function and role of a park at the gate of the housing complex, which has existed for a long time but has not been well maintained and only one year ago received assistance from the government in its arrangement and development. Since being renovated and repaired with the addition of huts, swings, slides and scales as well as the arrangement of ornamental trees, this park has been widely visited and is a representative children's playground. Through the implementation of the night market in the park environment, it will be able to increase the utility value of the park which is not only for playing but also as a place for art and improving the economy of the surrounding community. Through cooperation between the Community, Entrepreneurs (UMKM) Universities (through PKM activities) Related Agencies, the Cultural Conservation Center can realize the assistance of the Salamon Market night market as a means of creativity and growing the community's economy. With the scientific approach of management and procedures in managing an exhibition as the basis for organizing a market, a representative market event will be realized. The result of organizing Salamon Market is the realization of collaboration from various elements in making the market event a success in a public park and urban environment. The public's response can be seen from the number of participants in filling the art performance event, participating in stalls, watching the Bioling film screening, participating in healthy gymnastics, practicing batik, coloring motifs for children, and a batik fashion show for residents.